1996
DOI: 10.1128/aac.40.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of azithromycin by various cells and its intracellular activity under in vivo conditions

Abstract: The concentrations of azithromycin in polymorphonuclear leukocytes (PMNLs), monocytes, erythrocytes, and plasma were measured in six healthy volunteers after the last treatment of a 3-day regimen of 500 mg once daily. Marked enrichment of azithromycin was found in PMNLs and monocytes. The drug concentrations after the last dose amounted to 114 +/- 43 (mean +/- standard deviation) mg/liter at 12 h in PMNLs and 34 +/- 17 mg/liter at 6 h in monocytes. Fourteen days thereafter, azithromycin was still detectable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 10 publications
1
43
1
Order By: Relevance
“…This is possibly because susceptibility testing is based on serum drug levels, whereas for typhoid fever, a major mechanism of action is thought to be intracellular killing, in which the azithromycin levels may be 100-fold greater than serum levels [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is possibly because susceptibility testing is based on serum drug levels, whereas for typhoid fever, a major mechanism of action is thought to be intracellular killing, in which the azithromycin levels may be 100-fold greater than serum levels [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin, a member of the macrolide class of antibiotics, possesses many characteristics for effective and convenient treatment of typhoid fever, including in vitro activity against many enteric pathogens, excellent penetration into most tissues, and achievement of concentrations in macrophages and neutrophils that are 1100-fold higher than concentrations in serum [9][10][11]. Previous studies have demonstrated that a 7-day treatment course of azithromycin was highly effective against uncomplicated typhoid fever in adults and children [12][13][14].…”
mentioning
confidence: 99%
“…Azithromycin and clarithromycin accumulate in inflammatory cells, especially neutrophils and macrophages [5][6][7], inhibiting the synthesis of reactive oxygen species and/or secretion of cytokines and chemokines [3,[8][9][10][11]. Inhibition of adhesion molecule expression on epithelial cells, with suppression of leukocyte adhesion and infiltration into tissues has also been reported [3,8,12].…”
Section: Introductionmentioning
confidence: 98%
“…Although early relapses cannot be ruled out, they are very unlikely because these patients were followed up for only 28 days. Recrudescence might be due to the insufficient free plasma and intra-erythrocytic [17] concentrations of azithromycin resulting from an insufficient dosing and/or too short a duration of the treatment. To allow for this, we administered a higher dose of azithromycin for a longer (7-day) course.…”
Section: Discussionmentioning
confidence: 99%